Towards a conceptualization of the translator's legacy (2009)
This article investigates ways of theorizing the figure of the translator and its legacy within translation studies. It focuses on contemporary theoretical approaches, largely drawn from poststructuralist perspectives, which find the question of the translating subject to be a crucial one for translation and literary studies and propose important ways to approach it. It interrogates notions such as the idea of the sacralized original, the relationship between authorship and property, the ideal of transparent meaning, and the tension between translation and original writing. Particular attention is given to the importance of historicizing the translator's practice, recognizing the translator as a visible agent, and conceptualizing translation as a form of writing that unfolds within complex interactions and negotiations.